Review on the challenges of hybrid propulsion system in marine transport system - Damian, Sophea Elmmydya; Wong, Ling Ai; Hussain, Shareef; Vigna K., Ramachandaramurthy; Chan, C.K.; Moh, T.S.Y; Tiong, Meng Chung (Elsevier Ltd., 2022)
Hybrid propulsion systems have become more widely available as electrical systems and power supply equipment have become more integrated into maritime transportation over the past few decades. These benefits include improved compliance with international regulations, enhanced flexibility and reliability and decreased operating and maintenance costs. A key component in improving the performance of marine vessels' hybrid propulsion systems is the Battery Energy Storage System (BESS). The optimal sizing and operation must be ensured in order to fully use the installation of BESS onboard ships. This is one of the challenges associated with applying BESS in hybrid propulsion systems. This study presents a comprehensive overview of the challenges in implementing BESS to the hybrid propulsion systems found on modern commercial ships. Additionally, various technologies and the advantages of the BESS are covered. This paper concludes by addressing the future development of BESS control and performance to tackle increasingly challenging issues in the maritime transport hybrid propulsion system.